A New Biological Feature of Natural Killer Cells: The Recognition of Solid Tumor-Derived Cancer Stem Cells - Tallerico, Rossana; Garofalo, Cinzia; Carbone, Ennio (Frontiers in Immunology, 2016)
Natural killer (NK) cells are classified as a member of the innate lymphoid cells (ILCs) group 1. ILCs have been recently identified and grouped on the basis of their phenotypical and functional characteristics. They are effectors of innate immunity and are involved in secondary lymphoid organ generation and tissue remodeling. NK cells are powerful cytotoxic lymphocytes able to recognize and eliminate tumor- and virus-infected cells by limiting their spread and tissue damage. The recognition of tumor cells is mediated by both activating and inhibitory receptors. While in hematological malignancies the role played by NK cells is widely known, their role in recognizing solid tumors remains unclear. Recently, tumor cell populations have been divided into two compartments: cancer-initiating cells (CICs) or cancer stem cells (CSCs) and senescent tumor cells. Here, CSC will be used. CSCs are a small subset of malignant cells with stem-like properties that are involved in tumor maintenance and recurrence due to their ability to survive to traditional therapies; they are, moreover, poorly recognized by T lymphocytes. Recent data showed that NK cells recognize in vitro cancer-initiating cells derived from colon cancer, glioblastoma, and melanoma. However, more in vivo studies are urgently required to fully understand whether these new antitumor NK cells with cytotoxic capability may be considered in the design of new immunotherapeutic interventions.